Деякі напрями використання безпілотних літальних апаратів у слідчій та експертній практиці - Перлін, С. І.; Perlin, S. I.; Лозова, С. М.; Lozova, S. M. (Вісник Луганського держаного університету внутрішніх справ ім. Е. О. Дідоренка. – 2020. - № 1(89). - С. 269-279, 2020)
У статті розглянуто сучасний стан використання безпілотних літальних апаратів у криміналістичної діяльності. Проаналізовано нові засоби і методи, які можуть бути використані в криміналістичній діяльності, пов'язаній із фіксацією слідчих (розшукових) дій, а також у процесі проведення та оформлення результатів експертних досліджень на прикладі квадрокоптера DJI Mavic 2 Pro, який використовується в практичній діяльності Харківського науково-дослідного експертно-криміналістичного центру Міністерства внутрішніх справ України. Надано визначенняпоняття «безпілотний літальний апарат». Запропоновано криміналістичну класифікацію безпілотних літальних апаратів, що заснована на загальних підходах до систематизації техніко-криміналістичних засобів. Розглянуто основні технічні характеристики квадрокоптера DJI Mavic 2 Pro і його корисні функції. Сформульовано пропозиції щодо впровадження в слідчу та експертну практику безпілотних літальних апаратів.

In the article the current state of using of unmanned aerial vehicles in forensic activity, which is aimed at solving cognitive tasks during the detection and investigation of crimes, conducting certain investigative (search) actions, carrying out forensic researches, is considered. Attention is drawn to the fact that in modern period unmanned aerial vehicles are widely used by specialists in military equipment, civil defense and some other industries. However, their using is not yet widely used in investigative and expert practice. At the same time, expanding the scope of unmanned aerial vehicles as the mean of forensic technology will contribute to increase the efficiency of solving problems in the detection and investigation of criminal offenses. New means and methods that could be used for forensic activity connected with fixation of investigative (search) actions as well as the process of conducting and results of expert research on the example of the quadcopter DJI Mavic 2 Pro, which is used in the practical activity of the Kharkiv Scientific Research Forensic Center of the Ministry of Internal Affairs of Ukraine, are analyzed. The definition of unmanned aerial vehicles is suggested and terminological differences in concepts "drone" and "copter" are analyzed. The main classifications of unmanned aerial vehicles, which are used by specialists in military equipment and may have some forensic significance, are considered. The forensic classification of unmanned aerial vehicles that is based on common approaches to the systematization of technical and forensic means is suggested. The main criterion for the differentiation of unmanned aerial vehicles as technical and forensic means is the purpose of their using, because it defines the sphere of the using these means and the result of their using. The classification of unmanned aerial vehicles helps to facilitate the selection of their certain kind to perform investigative or expert task. The main technical characteristics of the DJI Mavic 2 Pro Quadcopter and its useful features such as flight on the proposed trajectory, functions of smart flight: Point of Interest and some others. Suggestions for the implementation in investigative and expert practice of unmanned aerial vehicles and scientific and practical recommendations for improving the process of training specialists in using the means, techniques and methods of forensic photo-, videoshooting with unmanned aerial vehicles are formulated.

В статье рассмотрено современное состояние использования беспилотных летательных аппаратов в криминалистической деятельности. Проанализированы новые средства и методы, которые могли бы быть использованы для криминалистической деятельности, связанной с фиксацией следственных (розыскных) действий, а также процесса проведения и результатов экспертных исследований на примере квадрокоптера DJI Mavic 2 Pro, который используется в практической деятельности Харьковского научно-исследовательского экспертно-криминалистического центра МВД Украины. Дано определение понятия «беспилотный летательный аппарат». Предложена криминалистическая классификация беспилотных летательных аппаратов, основанная на общих подходах к систематизации техникокриминалистических средств. Рассмотрены основные технические характеристики квадрокоптера DJI Mavic 2 Pro и его полезные функции. Сформулированы предложения по внедрению в следственную и экспертную практику беспилотных летательных аппаратов.
Some ways of using unmanned aerial vehicles in investigative and expert practice
Некоторые направления использования беспилотных летательных аппаратовв следственной и экспертной практике
Keywords: криміналістична техніка; безпілотні літальні апарати; техніко-криміналістичні засоби; фото-, відеозйомка слідчих дій; слідча та експертна практика; forensic technology; unmanned aerial vehicles; technical and forensic means; photo-, videoshooting of investigative actions; investigative and expert practice; криминалистическая техника; беспилотные летательные аппараты; технико-криминалистические средства; фото-, видеосъемка следственных действий; следственная и экспертная практика